DRIVING DIGITAL TRANSFORMATION FOR PUBLIC ACCOUNTING INNOVATION TOWARDS SDGs ALIGNMENT IN ASIA: BIBLIOMETRIC ANALYSIS WITH ADO-TCM FRAMEWORK - Jessica Hermawan; Andri Rianawati (Fakultas Ekonomi Universitas IBA, 2025)
This study investigates innovative public accounting models leveraging the ADO-TCM framework, emphasizing their alignment with SDGs 9, 11, and 16 and the transformative potential of digital governance. A systematic literature review (SLR) and bibliometric analysis using Scopus data from 87 articles are conducted to identify trends, co-occurrences, and citation networks. VOSviewer software is employed for visualizing research dynamics. Findings highlight that innovative public accounting models supported by ICT frameworks, AI-based decision-making, and data-driven systems enhance transparency, accountability, and efficiency. However, addressing regional disparities in ICT access and ensuring digital inclusivity remain challenges. Investments in ICT infrastructure and capacity-building are imperative to empower public accountant. The study contributes to narrowing governance disparities by providing actionable insights for policymakers. It underscores the importance of comprehensive, technology-driven governance strategies to enhance institutional effectiveness and stakeholder engagement. Future research should focus on the role of digital leadership, long-term impacts of governance models, and public-private collaboration.